High rejection self-oscillating up-conversion mixer for fifth-generation communications - Abdelhafid Es-saqy; Maryam Abata; Mohammed Fattah; Said Mazer; Mahmoud Mehdi; Moulhime El Bekkali; Catherine Algani (International Journal of Electrical and Computer Engineering (IJECE), 2023)
This paper presents the design of a pseudomorphic high electron mobility transistor (pHEMT) self-oscillating mixer (SOM) for millimeter wave wireless communication systems. The 180Â° out-of-phase technique is chosen to both improve the desired lower sideband (LSB) signal and to achieve a satisfactory rejection of the unwanted signals (LO, USB and IF). This SOM is designed on the PH15 process of UMS foundry which is based on 0.15 Âµm GaAs pHEMT. The signal is up-converted from 2 GHz-IF frequency to 26 GHz-LSB frequency, using an autogenerated 28 GHz-LO signal. Simulations were performed using the advanced design system (ADS) workflow. They show 6.4 dB conversion gain and a signal rejection rate of 29.7 dB for the unwanted USB signal. the chip size is 3.6 mm2.